Household Financial Management Training for Housewives Stairs during the COVID-19 Pandemic Period in Margasari Village - Octaviani, Intan; Sasmita, Djenni (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
This activity aims to provide insight and knowledge to housewives in managing household finances properly and correctly, so that revenues are greater than expenses. There is an amount of money from household cash that can be used as savings / investment that is saving in the future, so that a prosperous life can be realized for the family economy. The method used in this activity is training or short training in household financial management using the financial management module. The participants received training using the classical method of providing materials, question and answer sessions, exercises / practices; providing working papers that are inputted according to the real economic conditions of the participants. The object of research as activity participants, namely housewives who do not work, housewives who work, and housewives who have businesses with an average high school educational background, as well as an economic background from middle to lower families can participate in the training properly. and full of enthusiasm. The results of this service provide support so that housewives avoid high interest money loans. For further community service activities, it is hoped that they will be able to provide continuous training that triggers the spirit of housewives to learn to invest.